2018
DOI: 10.3390/w10040500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Structural, Chlorophyll-Based and Photochemical Indices to Detect Summer Maize Responses to Continuous Water Stress

Abstract: This study evaluates the performance of structural, chlorophyll-based, and photochemical indices to detect maize water status and to assess production based on five years of field experiments (2013-2017) during the primary growth stages. We employed three categories of indicators, including water condition and productive and thermal indicators, to quantify the responses of summer maize under continuous water stress from drought to waterlogging conditions. Furthermore, we adopted several spectral indices to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
5
13
1
1
Order By: Relevance
“…This situation combined with transpiration loss of water would force plants to reduce their leaf area to adapt to the water conditions imposed on them. A sharp reduction in leaf growth parameters including width, length and leaf area of maize was obtained under water stress conditions (Avramova et al, 2016;Li et al, 2018). Or the intercepted radiation proportion is estimated from the leaf area which is therefore an important variable in crop production determination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation combined with transpiration loss of water would force plants to reduce their leaf area to adapt to the water conditions imposed on them. A sharp reduction in leaf growth parameters including width, length and leaf area of maize was obtained under water stress conditions (Avramova et al, 2016;Li et al, 2018). Or the intercepted radiation proportion is estimated from the leaf area which is therefore an important variable in crop production determination.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a decrease in chlorophyll content was observed in corn under water stress conditions compared to non-stress. (Avramova et al, 2016;Ahmad et al, 2017;Li al., 2018). On the other hand, Adra (2010) found an increase in total chlorophyll content and Amoumen et Benhebireche (2013) obtained decrease in chlorophyll content in water stress conditions in durum wheat.…”
Section: Discussionmentioning
confidence: 99%
“…On another level, the Red-Edge domain also seems to be of particular interest. This domain gives insight into leaf chlorophyll concentration [62,68,69], which is itself related to the availability of water in the plant [70][71][72]. The "Red-Edge" domain has already been linked to the water status of the vine by [20], who estimated crop coefficient (Kc) using a time series of Sentinel-2 images, or by [73], who correlated stem water potential and UAV data.…”
Section: Spectral Domain and VI Sensitivitymentioning
confidence: 99%
“…Moreover, structural related VIs such as NDVI, rNDVI, OSAVI, EVI, and REIP showed significant effects between soil water levels (Table 4) and significantly positive relations between these VIs with g s and T r (Figure 6 and Figure S4). In recent studies, structural VIs have also successfully been used to predicted water stress proxies (e.g., g s , leaf water content, and leaf water potential) in maize plants [91,92]. In our study, the effect of growth through these VIs is shown by the high sensitivity of phenology (DoM), lack of significance with soil drought (WHC) (Table 4), and the strong positive correlations with h c (R 2 > 0.86) (Figure 6 and Figure S4).…”
Section: Physiological Biochemical Morphological and Remote Sensing Responses Under Water Stressmentioning
confidence: 99%